2008
DOI: 10.1002/art.23203
|View full text |Cite
|
Sign up to set email alerts
|

A six‐month randomized controlled trial of exercise and pyridostigmine in the treatment of fibromyalgia

Abstract: Objective. A subset of fibromyalgia (FM) patients have a dysfunctional hypothalamic-pituitary-insulinlike growth factor 1 (IGF-1) axis, as evidenced by low serum levels of IGF-1 and a reduced growth hormone (GH) response to physiologic stimuli. There is evidence that pyridostigmine (PYD) improves the acute response of GH to exercise in FM patients. The purpose of this study was to evaluate the clinical effectiveness of 6 months of PYD and group exercise on FM symptoms.Methods. FM patients were randomized to 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 37 publications
2
62
1
1
Order By: Relevance
“…Care was taken in the design of the study protocol [18]; all patients underwent clinical examination at monthly intervals; and medication for Wbromyalgia was restarted if necessary. Patients in the WA and MS groups took less medication, which is consistent with the Wndings of other study, which had reported that the aerobic exercise group took fewer analgesics than did the controls [12].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Care was taken in the design of the study protocol [18]; all patients underwent clinical examination at monthly intervals; and medication for Wbromyalgia was restarted if necessary. Patients in the WA and MS groups took less medication, which is consistent with the Wndings of other study, which had reported that the aerobic exercise group took fewer analgesics than did the controls [12].…”
Section: Discussionsupporting
confidence: 86%
“…However, these studies have used diVerent combinations of exercise modalities [10][11][12][13], making it diYcult to determine which modality is in fact eVective. There are few evidences that strengthening exercises, as a single modality [1,[14][15][16][17], improve Wbromyalgia symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Pyridostigmine, a medication which increases the secretion of endogenous growth hormone, has been tested in FMS but did not show efficacy [59]. In a trial testing the interaction of pyridostigmine (mestinon) and exercise in FMS, the group treated with pyridostigmine showed improvement in parameters of anxiety and sleep, while exercise improved fatigue and fitness [60].…”
Section: • • Growth Hormone Agonistsmentioning
confidence: 99%
“…Pyridostigmine, a medication which increases the secretion of endogenous growth hormone, has been tested in FMS but did not show efficacy [120].…”
Section: Ibutamoren Mesylatementioning
confidence: 99%